Trends in Between-Country Health Equity in Sub-Saharan Africa from 1990 to 2011: Improvement, Convergence and Reversal - Jin, Jiajie (Int J Environ Res Public Health, 2016)
It is not clear whether between-country health inequity in Sub-Saharan Africa has been reduced over time due to economic development and increased foreign investments. We used the World Health Organization’s data about 46 nations in Sub-Saharan Africa to test if under-5 mortality rate (U5MR) and life expectancy (LE) converged or diverged from 1990 to 2011. We explored whether the standard deviation of selected health indicators decreased over time (i.e., sigma convergence), and whether the less developed countries moved toward the average level in the group (i.e., beta convergence). The variation of U5MR between countries became smaller from 1990 to 2001. Yet this sigma convergence trend did not continue after 2002. Life expectancy in Africa from 1990–2011 demonstrated a consistent convergence trend, even after controlling for initial differences of country-level factors. The lack of consistent convergence in U5MR partially resulted from the fact that countries with higher U5MR in 1990 eventually performed better than those countries with lower U5MRs in 1990, constituting a reversal in between-country health inequity. Thus, international aid agencies might consider to reassess the funding priority about which countries to invest in, especially in the field of early childhood health.